Changes in plasma concentration of cell-free DNA in response to physical activity - Hubacek, Jaroslav A; Dlouhá, Dana; Wünsch, Hana; Slabý, Kryštof; Oreská, Sabína; Prokopcová, Aneta; Rybář, Marian; Vrablik, Michal; Tomčik, Michal (Archives of medical science, 2025)
INTRODUCTION: Plasma concentrations of cell-free DNA (cfDNA) serve as markers of overtraining or muscle injury. We examined whether nuclear (n) or mitochondrial (mt) cfDNA has potential as a marker of muscle burden or damage. MATERIAL AND METHODS: Ten healthy, physically active volunteers (6 females, aged 27.1 ±6.8 years) performed a downhill running test. Samples for cfnDNA and cell-free mitochondrial DNA (cfmtDNA) analysis were collected before, 30 min, 1 h, and 14 days after the downhill run. CfnDNA and cfmtDNA (two markers for each) were analyzed using qPCR. RESULTS: There was an extreme (~40-fold) increase in cfnDNA at the 30-min time-point against the baseline (p < 0.00001 for both markers), followed by a quick drop to baseline levels after 1 h after the end of the downhill run for all subjects. In contrast, plasma levels of cfmtDNA did not increase significantly (p = 0.27 and 0.12). It reflects the fact that in 6 subjects, the pattern was similar as for cfnDNA, but in 4 subjects a decrease of cfmtDNA concentration was observed at the 30-min time-point. These differences correlate with age, body mass index, and sex of the participants. Plasma cfnDNA significantly (p < 0.01 for all) correlated with concentrations of muscle damage markers such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), and lactate dehydrogenase (LD), and chemokines MIP-1α and IP-10 (positive). No homogeneous correlation between cfmtDNA and biomarkers was detected. CONCLUSIONS: Our study confirmed the extreme release and clearance of cfnDNA in physically active subjects after strenuous exercise. In contrast, the trajectory of cfmtDNA concentrations seems to have much higher inter-individual variability than cfnDNA concentrations.
Keywords: cell-free DNA; physical activity; nucleus; mitochondria